Legal Protection for Creditors Holding Warehouse Receipt Security Rights According to Indonesian Law - Sholehuddin; Kholid (Penerbit Hellow Pustaka, 2025)
The purpose of this study is to examine and analyze the creditors who hold the right to guarantee warehouse receipts in the form of legal protection for creditors who are harmed by debtors who have defaulted on their promises/breach of contract, resulting in legal uncertainty. The form of legal protection for creditors as holders of the right to guarantee warehouse receipts is regulated in Article 27 paragraph (2) of the Law on Warehouse Receipt Systems and Article 40 letter k of Government Regulation Number 36 of 2007 concerning the implementation of Law Number 9 of 2006 concerning the Warehouse Receipt System, namely requiring warehouse managers to insure the goods stored as collateral and requiring warehouse managers to pay compensation to the receipt holder if there is a loss and/or damage to the goods due to negligence.